Experimental Manipulation of Pectin Architecture in the Cell Wall of the Unicellular Charophyte, Penium Margaritaceum - Palacio-Lopez, Kattia; Sun, Li; Reed, Reagan; Kang, Eric; Sørensen, Iben; Rose, Jocelyn K. C.; Domozych, David S. (Frontiers in Plant Science, 2020)
Pectins represent one of the main components of the plant primary cell wall. These polymers have critical roles in cell expansion, cell-cell adhesion and response to biotic stress. We present a comprehensive screening of pectin architecture of the unicellular streptophyte, Penium margaritaceum. Penium possesses a distinct cell wall whose outer layer consists of a lattice of pectin-rich fibers and projections. In this study, cells were exposed to a variety of physical, chemical and enzymatic treatments that directly affect the cell wall, especially the pectin lattice. Correlative analyses of pectin lattice perturbation using field emission scanning electron microscopy, confocal laser scanning microscopy, and transmission electron microscopy demonstrate that pectin lattice microarchitecture is both highly sensitive and malleable.